Early-TIPS Versus Current Standard Therapy for Acute Variceal Bleeding in Cirrhosis Patients: A Systemic Review With Meta-analysis - Shuang Li; Chao Zhang; Lu-Lu Lin; Qi Wang; Hong-Xia Zuo; Ai-Ling Zhan; Jie Luo; Yu-Ming Niu; Guo-Qing Zhong (Frontiers Media S.A., 2020)
BackgroundThe survival of early placement (within 72h after admission) of transjugular intrahepatic portosystemic shunts (early-TIPS) in patients with cirrhosis and acute variceal bleeding (AVB) is controversial.ObjectivesWe performed a systemic review and meta-analysis to assess whether early-TIPS could improve survival in patients with cirrhosis and acute variceal bleeding.MethodsA systematic search of the literature was conducted in PubMed, EMBASE, and Cochrane Library published before 25 June 2019 for eligible studies that compared early-TIPS with a combination of endoscopic variceal ligation (EVL) and pharmacotherapy in the therapeutic effect in AVB patients.ResultsA total of five studies with 1,754 participants were enrolled. The early-TIPS demonstrated a significant improvement in prevention of treatment failure (OR=0.11,95%CI=0.05-0.23), 6-weeks mortality (OR=0.24,95%CI=0.13-0.46), rebleeding within 6 weeks (OR=0.21,95%CI=0.12-0.36), rebleeding within 1 year (OR=0.16,95%CI=0.07-0.36), new or worsening ascites (OR=0.33,95%CI=0.21-0.53), except in encephalopathy (OR=1.29,95%CI=0.996-1.67). For 1-year mortality, a significant prior effect was also observed in early-TIPS (OR=0.64,95%CI=0.46-0.90), and the beneficial effect in Child-Pugh C patients (OR=0.35,95%CI=0.18-0.68) was equal to Child-Pugh B patients (OR=0.34,95%CI=0.25-0.58). No difference in liver transplantation and mortality caused by liver failure was observed.ConclusionsEarly covered-TIPS could be recommended for the management of AVB patients in cirrhosis demonstrating a significant improvement in treatment failure, both short- and long-term mortality, rebleeding risk, and new or worsening ascites compared to standard therapy, especially for high-risk AVB patients. It will also apply to patients with Child-Pugh A until solutions to prevent hepatic encephalopathy in future research are found.